The Role of Social Capital in the Development of Mauhalek Waterfall Ecotourism in Belu District, East Nusa Tenggara Province - Klau, Nopriyan Petrus; Affandi, Aminudin; Nugroho, Iwan (Graduate School, Universitas Brawijaya, 2019)
The purpose of this research is to know the relationship and the role of social capital in supporting product and service of Mauhalek waterfall ecotourism. Phenomenology approach was chosen because it allow the researcher to identify a particular phenomenon, and requires the researcher to examine the subject by being directly involved in developing meaningful patterns and relationships. In the context of the research to be studied, the main focus of this research is the norms, beliefs, networks, products, and services of Mauhalek waterfall. From the research results, it can be concluded that there are various custom rules in maintaining Mauhalek waterfall which still exists until now, one of them is ukum Badu (prohibition of cutting the tree and taking fruit that existing around the Mauhalek forest). The high belief in myths and rules makes the sustainability of Mauhalek waterfall is still maintained until now. The beauty and authenticity of natural resources and culture of Mauhalek waterfall make it as a good tourist product to be offered to the visitor.Keywords: Mauhalek waterfall, social capital, sustainable tourism.